THE PERSPECTIVE OF CORPORATE GOVERNANCE ON THE INTERACTIONS OF INTERNAL AUDIT WITH MANAGMENT AND ITS IMPACT ON THE INTERNAL - EXTERNAL AUDIT LINKAGES - Dawit Tadesse Tiruneh (Copernican Journal of Finance & Accounting, 2021)
Literatures based on developed countries suggest an interaction of internal audit with management has impact on the internal-external audit linkages and the interactions and linkages have their own contribution toward the realization of good corporate governance. Nevertheless, these interactions have not been sufficiently explored in developing countries such as Ethiopia. This quantitative research examines in the form of explanatory study the interaction of internal audit with management and its impact on the internal- external audit linkages in Ethiopia. By doing so, it explained the causal relationship between variables through hypothesis testing. The research method of this study was a constructed questionnaire, which was sent to companies and to the 100 top management, internal auditors, and external auditors in Ethiopia. As it has been examined, existing findings suggest that organizations can enhance corporate governance’s effectiveness by strengthening the interactions of internal audit with management and in the meantime as the result of this impact by upgrading the internal-external audit linkages. In line with this, the results indicate interactions of internal audit with management depend on the level of the result of internal audits’ effectiveness, as the result, it positively moderates the internal-external audit linkages.